Crossover from Ferroelectric to Relaxor Behavior in Ba(1−x)Ca(x)TiO(3) (x = 0.17) System - Palaimiene, Edita (Materials (Basel), 2020)
The dielectric properties of Ba(1−x)Ca(x)TiO(3) (x = 0.17) ceramics were studied in a wide frequency range of 20 Hz–53 GHz. Diffused ferroelectric phase transition was revealed close to 339 K in the dielectric properties of ceramics. The behaviour of distributions of relaxation times in vicinity of the ferroelectric phase transition temperature is also typical for order-disorder ferroelectric phase transition. However, at lower temperatures (below 200 K), the most probable relaxation increased according to the Arrhenius law. At lower temperatures the maximum of the imaginary part of dielectric permittivity versus temperature strongly shifted to higher temperatures when the frequency increased (from 125 K at 1.21 kHz to 300 K at 33 GHz). This behaviour was attributed to the dynamics of Ti ions. The origin of the crossover from ferroelectric to relaxor behaviour of Ba(1−x)Ca(x)TiO(3) (x = 0.17) ceramics is discussed in the paper.